Profiles of School Burnout among Polish Late Adolescents and Its Association to the Quality of Family Bonds - Tomaszek, Katarzyna; Muchacka-Cymerman, Agnieszka (Przegląd Psychologiczny, 2024)
Aim: The family environment is generally recognized as an important factor in protecting from school burnout syndrome, though mostly for younger students. Importantly, the differences in experiencing school burnout and family characteristics are still rarely examined, especially among late adolescents in Poland. For an in-depth understanding of school burnout patterns among Polish youth, this research has undertaken a person-centered, latent profile analysis of school burnout. Additionally, this paper sought to determine whether family bonds interact with demographic characteristics (gender, age) in predicting school burnout among late secondary school students. Method: A total of 964 late school students (Mage = 18.18, SD = 0.48 years; 65% girls) were surveyed using the Student School Burnout Scale (SSBS), and the 1-item quality of family bonds indicator. Results: Five distinct School Burnout component profiles emerge, for example one profile with severe school burnout symptoms: Uninterested in learning (9.4% of the sample), three profiles with moderate levels of burnout for example Exhausted with studying, Struggling with school duties, Incompetent. Finally, students of the last profile presented low levels of school burnout total score and the average in some domains, for example Fatigue with learning activities. These profiles indicate significant differences in family bonds, age and gender. Family bonds significantly interacted with age and gender when explaining school burnout in the total sample. Simple slope analyses revealed that the positive association between gender or age and school burnout was greater under the condition of less positive family bonds. Girls and older adolescents from families with the most negative bonds were more likely to develop school burnout. Additional analyses conducted separately for each profile revealed the significance of the interaction between gender and family bonds in profiles with the highest scores in SSBS (Profile 2, 4). Conclusions: The study confirmed that living in unfavorable family environments is a risk factor for school burnout; however, it is mostly observed among girls experiencing burnout who are less resistant to this condition. Our findings contribute to the discourse related to the gap in the burnout literature, indicating the need for conducting school burnout interventions that are focused on both school and family environments.